Dynamic compressive behaviour of cellular materials: A review of phenomenon, mechanism and modelling - Sun, Yongle; Li, Q.M. (International journal of impact engineering, 2018)
•Dynamic plastic properties, deformation modes, constitutive relations and shock states are described.•Experimental observations in the quasi-static, transitional dynamic and shock regimes are presented.•Mechanisms associated with inertia, enclosed gas and microscopic strain-rate sensitivity of base material are elucidated.•Mesoscopic modelling and its applications are discussed with regard to idealised and realistic cell structures.•Macroscopic continuum-based modelling for compression-dominated loading is summarised and commented. Dynamic compressive behaviour of cellular materials is crucial to their applications in energy absorption, ballistic mitigation and blast/impact protection. The recent research progress in this subject has led to an improved understanding of the experimental, analytical and numerical observations. This review focuses on the aspects of phenomena, mechanisms and modelling on the concerned subject. Attention is paid to linking macroscopic dynamic compressive behaviour with the subscale influential factors. The characteristics of cellular materials at different spatial scales and their compressive behaviours at different loading rates are introduced, based on experimental observations in the quasi-static, transitional dynamic and shock regimes of compression. Then a comprehensive discussion about the roles of the micro- and meso-scale mechanisms in the dynamic compressive behaviour is presented. Finally, important modelling approaches and results are reviewed and commented. The main conclusions are: (1) the strain-rate sensitivity of cellular materials is closely associated with base material properties (both quasi-static and dynamic ones) and cell structure; (2) the compaction shock in cellular materials has mesoscopic structural causes and its formation leads to unique deformation mode, load transmission and stress–strain states; (3) shock initiation requires sufficient loading rate or intensity, and its critical condition can be described based on impact velocity; (4) cell-based modelling is useful for the identification and examination of the underpinning mechanisms, while continuum-based modelling is necessary for the analysis of structures made of cellular materials. Outstanding issues on the subject of the dynamic compressive behaviour of cellular materials are also addressed.